Quantum computers: prospects for changing the world - Tereshchenko, V. (НГУ, 2018)
Quantum computers are a class of physical devices that follow the quantum mechanics laws to perform high-speed mathematical and logical operations, storing and processing quantum information. The main purpose of studying these computers is to solve the problem of energy consumption in computers.
Keywords: quantum computers; quantum information; problem of energy consumption in computers